2009
DOI: 10.1902/jop.2009.080542
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Gingival Crevicular Blood for Measuring Glucose to Screen for Diabetes: An Examination Based on Characteristics of the Blood Collection Site

Abstract: GCB samples were suitable to screen for diabetes in persons with sufficient BOP to obtain a sample without touching the tooth or gingival margin (i.e., in patients having the basic clinical signs of gingivitis or periodontal disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 43 publications
1
39
1
Order By: Relevance
“…This finding of the present study is consistent with the most of previous studies of Wu et al, 11 Ardakani et al, 12 Shetty et al, 13 and Strauss et al 14 on the correlation between gingival crevicular and capillary blood glucose levels who also reported that GCB samples are suitable to screen for DM in individuals with sufficient bleeding on probing (BOP).…”
Section: Resultssupporting
confidence: 93%
“…This finding of the present study is consistent with the most of previous studies of Wu et al, 11 Ardakani et al, 12 Shetty et al, 13 and Strauss et al 14 on the correlation between gingival crevicular and capillary blood glucose levels who also reported that GCB samples are suitable to screen for DM in individuals with sufficient bleeding on probing (BOP).…”
Section: Resultssupporting
confidence: 93%
“…12 Since periodontal inflammation with or without complication factor of DM is known to produce ample extravasate of blood during diagnostic periodontal examination, it can be used for the routine random blood glucose level estimation. 13 Strauss et al 14 also reported that GCB samples were suitable in persons with sufficient bleeding on probing, to obtain a sample without touching the tooth or the gingival margin (i.e., in patients having the basic clinical signs of gingivitis or periodontal disease). Moreover, the technique is more familiar and less traumatic to the patient than a finger puncture.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Strauss et al in their study reported that gingival crevicular samples are suitable to screen for diabetes in individuals with suffi cient bleeding on probing. [13] Sarlati et al stated in patients with diabetes this method revealed suffi cient agreement. [14] Hence, they concluded that gingival crevicular blood can be used for testing blood glucose level during the periodontal examination in diabetic periodontal patients but not in non-diabetics.…”
Section: Discussionmentioning
confidence: 99%